THOUGHT FOR FOOD : THE SOCIAL AND CULTURAL ASPECTS OF MALNUTRITION - Balcomb, Jonn (SCHOOL SCIENCE, 2012)
Derrick B. Jelliffe, a silm Englishman in his fifties, has probably done as much as any person now living to focus attention on practical solutions to the problem of malnutrition among young children in the developing countries. Jelliffe, formerly UNICEF Professor of Paediatrics at Makerere University in Kampala, Uganda, and presently Director of the Caribbean Food and Nutrition Institute in Kingston, Jamaica, is not a science celebrity. He has never won a Nobel Prize and has no outstanding biochemical research to his credit. He is basically a field worker, a teacher, and an indefatigable polemicist, addressing himself ceaselessly to the medical and nutritional fraternity in language it understands and through its chosen organs of communications.